A Nonlinear Relation Between Maternal Red Blood Cell Manganese Concentrations and Child Blood Pressure at Age 6–12 y: A Prospective Birth Cohort Study. Issue 3 (12th January 2021) - Wang, Guoying; Tang, Wan-Yee; Wills-Karp, Marsha; Ji, Hongkai; Bartell, Tami R; Ji, Yuelong; Hong, Xiumei; Pearson, Colleen; Cheng, Tina L; Wang, Xiaobin
ABSTRACT: Background: Although manganese (Mn) is an essential trace element and a common component of most multivitamins on the market, an adverse effect on blood pressure (BP) has been reported in adults. In addition, the longitudinal relation between prenatal Mn status and childhood BP is still unknown. Objective: This study investigated the association between prenatal Mn concentrations and risk of elevated BP at ages 3–12 y. Method: The analyses included 1268 mother-child dyads who were enrolled at birth and followed prospectively at the Boston Medical Center. Maternal RBC Mn concentrations were measured by inductively coupled plasma mass spectrometry, using RBCs collected within 1–3 d after delivery (reflecting late-pregnancy Mn exposure). Child elevated BP was defined as systolic or diastolic BP ≥90th percentile for a given age, sex and height. Multivariate logistic regression models were conducted. Path analysis was applied to mediation estimation. Results: The median (IQR) maternal RBC Mn concentration was 37.5 (29.2–48.5) μg/L. The rate of child elevated BP at ages 3–12 y was 25%. Both the lowest and highest quartiles of maternal RBC Mn concentrations were associated with higher risk of elevated BP among children aged 6–12 y (OR: 1.52; 95% CI: 1.04, 2.21 and OR: 1.65; 95% CI: 1.13, 2.40, respectively) compared with those in the second and third quartiles. Gestational age and fetal growth mediated the association between low maternal RBC Mn (first quartile) and child elevated BP, explaining 25% of the association, but not for high (fourth quartile) maternal RBC Mn concentrations. No association was found between maternal RBC Mn concentrations and BP among children aged 3–5 y. Conclusion: We found a nonlinear association between maternal RBC Mn concentrations and elevated BP among children aged 6–12 y from a high-risk, predominantly minority population. Our findings warrant further investigation.